Well-Being At Work: A Study With Social Educators - Fernandes, Rosina (2021)
Employee health and well-being are on organizations leaders’ agendas, including in the social area. So, this study aimed to explore the associations between job satisfaction and other well-being at work variables (success, salary, and occupation’s prestige) in a recent social sector profession. Also, intended to reflect on its importance in promoting health and well-being in workers who daily deal with other’s suffering. This quantitative study involved 74 employed Portuguese Social Educators, 94.6% female with mean age of 30.12±8.94. A questionnaire was specifically prepared for this research project, given the scarcity of studies about well-being at work in Social Education area. SPSS 25 was used for data analysis, assuming a 95% confidence level. Job satisfaction was positively correlated (p≤.05) with success and prestige. Salary was relevant (p≤.05) to job satisfaction, regardless of whether the professionals were working in the training area. In those who were, job satisfaction was also correlated with the desire to keep the job (p=.002). Participants with higher success, career satisfaction and prestige were more optimistic about professional future (p≤.05). Given the Social Educators intervention in high risk and social vulnerability contexts, work benefits such as access to counselling or other health initiatives preventing occupational stress and burnout, may be an effective alternative to salary increase, often difficult to social organizations. It’s effect on satisfaction and success, together with growing social recognition of profession is essential for these workers well-being.